Preparing Culturally Competent Practitioners for a Global Society - Vivian Mott; Steven Schmidt (Adult Education Research Conference, 2007)
The purpose of this mixed design research was to explore the cultural competency of adult education and counseling graduates in multicultural practice environments. While race/ethnicity, age, and experience influence cultural attitudes and competencies, effective graduate education, as well as mentoring and modeling by faculty, significantly improve cultural competency of new practitioners.